Hazard identification and exposure assessment for bacterial risk assessment of informally marketed milk in Abidjan, Côte d'Ivoire - Kouamé-Sina, S.M.; Makita, K.; Costard, Solenne; Grace, Delia; Dadie, A.; Dje, M.; Bonfoh, Bassirou (2012)
Background. Animal-source foods are important causes of food-borne illness, and milk and dairy products can contain pathogenic microorganisms. Objective. We conducted a stochastic assessment of the risk of ingesting milk contaminated with specific microbial pathogens (Escherichia coli, Staphylococcus aureus, and Enterococcus spp.) in Abidjan, Côte d'Ivoire. Methods. We carried out structured interviews and focus group discussions with farmers (n = 15), vendors (n = 17), and consumers (n = 188) to characterize dairy production systems and milk consumption behavior. Microbiological sampling was conducted at different points between milking and sale. A risk model was developed, and the risk of consuming contaminated raw milk was estimated by Monte Carlo simulation. Results. The investigation into local raw milk consumption patterns showed that the proportion of raw milk consumption was 51.6% in people who consume milk. The probability of ingestion of marketed raw milk that failed to meet standards for this group of bacteria was 29.9% and about 652 consumers per day were estimated to ingest contaminated milk. Microbiological tests from the farm showed that 7.2% of samples taken from milkers' hands, 4.4% of water samples (water used to rinse milk containers or milking utensils (calabash, plastic bottle, filters, buckets), 4.4% of environmental samples (air pollution), 13.2% of samples from milking utensils, and 4.9% of samples from cows' udders were contaminated with one or more of these pathogens. About 624.6 L of marketed raw milk would need to be discarded per day if discarding milk was chosen as the option of risk reduction. The destruction of this milk would result in a potential loss of €623.9 per day for all producers. Conclusions. The risk of human illness from consumption of raw milk could be mitigated by raising awareness about heat treatment of milk and good hygiene practices in the dairy chain.